(untitled) (REMUNOM, 2026)
Arboviral diseases transmitted by Aedes aegypti represent a major public health challenge in tropical regions, particularly in Brazil, where environmental and urban factors favor the proliferation of this vector. In this context, plant-derived products such as essential oils have been investigated as sustainable alternatives to synthetic insecticides. This study aimed to evaluate the chemical composition, larvicidal activity, and toxicity of the essential oil from Origanum vulgare L. collected in the Brazilian Legal Amazon against Aedes aegypti. The essential oil was obtained by hydrodistillation using a Clevenger-type apparatus and analyzed by gas chromatography coupled with mass spectrometry (GC–MS). Larvicidal activity was assessed using third-instar larvae of A. aegypti following the World Health Organization protocol, while toxicity was evaluated through the Artemia salina lethality bioassay. The essential oil yield was 1.9%, with a predominance of monoterpenes (93.03%), mainly terpinolene (27.89%), γ-terpinene (19.03%), carvacrol (14.28%), and terpinen-4-ol (13.75%). The oil showed relevant larvicidal activity, with LC₅₀ of 95.6 µg/mL and LC₉₀ of 254,7 µg/mL, indicating potential for vector control. However, the toxicity assay revealed an LC₅₀ of 76.6 µg/mL for Artemia salina, classifying the oil as highly toxic to this organism. These findings indicate that the essential oil of O. vulgare has potential as a natural larvicidal agent, although further ecotoxicological studies are required to assess its safety and applicability in vector control programs.